The Design Of Arduino Prototype For Monitoring Septic Tank Using Message Gateway - Setia Susilawati; Sunarsan Sitohang (Merdeka Malang University, 2020)
The housing that is currently being built usually only has a small septic tank, which can lead to problems with the tank if the tank is full. Starting from the blocked septic tank can even explode. The purpose of this research is to make prototype in monitoring a tank in a septic tank with Message Gateway. The tools used in this study are Arduino Uno which is tntegrated with ultrasonic sensors, MQ-2 sensors and SIM800L Modules, after which the LCD receives data from Arduino and is displayed on the LCD followed by a LED light. And fro SIM800L it will automatically send a short message. The result of this research if this study after Arduino processed data from the HC-SR04 Ultrasonic Sensor and MQ-2 Sensor then the sensor sent a signal to SIM800L and SIM800L sent a Message to the user with a warning of 30%, 50% and 100% water level septic tank. The MQ-2 sensor can only detect gas in the septic tank, if the gas in the septic tank is more than 15.000 ppm it will automatically send a Message to the user that the Danger Gas, which indicates that this prototype has been running as expectedDOI : https://doi.org/10.26905/jeemecs.v3i2.4404